Confirmation - Gregson-Williams, Harry 1961- (HBO Home Box Office, 2016)
Look behind the curtain of Washington politics, depicting the explosive 1991 Clarence Thomas Supreme Court nomination hearings where Anita Hill accused him of sexual harassment. The hearings brought the country to a standstill and became a pivotal moment in American culture forever changing how people perceive and experience workplace equality and gender politics
"Confirmation mit Kerry Washington (Scandal), Wendell Pierce (The Wire) und Greg Kinnear (Besser geht's nicht) in den Hauptrollen führt uns hinter die Kulissen der amerikanischen Politik: 1991 kommt es zum Eklat, als Clarence Thomas für das Oberste Bundesgericht nominiert wird, denn Anita Hill bezichtigt ihn der sexuellen Belästigung. Rick Famuyiwa (Dope) inszenierte das Drehbuch von Susannah Grant (Oscar-Kandidatin für Erin Brockovich) und zeigt einen Schlüsselmoment in der amerikanischen Kultur, der sich zum Wendepunkt der Gleichstellungspolitik im Kampf der Frauen für faire Behandlung am Arbeitsplatz entwickelte." (Rückseite der DVD-Hülle)
"Specials: Kerry Washington über die historische Bedeutung, Wendell Pierce über die historische Bedeutung, 'Confirmation': über die Hauptfiguren" (Rückseite der DVD-Hülle)
Fernsehfilm, USA 2016
Besetzung: Kerry Washington (Anita Hill), Wendell Pierce (Clarence Thomas), Greg Kinnear (Joe Biden), Jeffrey Wright (Charles Ogletree), Eric Stonestreet (Ken Duberstein), Bill Irwin (Jack Danforth), Zoe Lister-Jones (Carolyn Hart), Grace Gummer (Ricki Seidman), Treat Williams (Ted Kennedy), Dylan Baker (Orrin Hatch), Erika Christensen (Schirley Wiegand), Alison Wright (Ginni Thomas), Malcolm Gets (Arlen Specter), Peter McRobbie (Alan Simpson), Kimberly Elise (Sonia Jarvis), Jennifer Hudson (Angela Wright); Musik: Harry Gregson-Williams, Kostümdesign: Hope Hanafin, Kamera: Rachel Morrison, Szenenbild: Stephen Altman
Keywords: Hill, Anita -- 1956-; Thomas, Clarence -- 1948-; Judges / Selection and appointment / United States / Drama; Sexual harassment of women / United States / Drama; United States / Supreme Court; Judges / Selection and appointment; Sexual harassment of women; United States / https://id.oclc.org/worldcat/entity/E39PBJtxgQXMWqmjMjjwXRHgrq; Biographical films; Biographical television programs; Drama; Feature films; Fiction television programs; Made-for-TV movies; Film; Fernsehsendung; DVD-Video